Lithium ion secondary battery

By using silicon-carbon composite materials and specific electrolyte combinations in lithium-ion batteries, the problems of low energy density and large volume expansion in lithium-ion batteries are solved, the cycle stability and high temperature storage performance of the battery are improved, and the high energy density is achieved It takes into account both fast charging.

CN119208731APending Publication Date: 2024-12-27ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411326144.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The energy density of graphite materials in existing lithium-ion batteries is low, and the volume of silicon-based materials expands during charging and discharging, resulting in fast cycle attenuation and limited rapid charging capacity. The dissolution problem at high voltages is serious, affecting the safety performance of the battery.

Method used

Silicon-carbon composite material is used in the negative electrode sheet of lithium-ion secondary battery, and lithium difluorosulfonimide and fluorovinyl carbonate are added to the electrolyte. By adjusting the proportion of these components, a specific relationship is met to improve The battery's cycle stability and high-temperature storage performance take into account high energy density, low thickness expansion rate and fast charging capability.

Benefits of technology

Through the combination of silicon-carbon composite materials and specific electrolytes, the volume expansion rate of the negative electrode material is reduced, the cycle stability and high-temperature storage performance of the battery under high voltage are improved, the energy density and fast charging capacity of the battery are enhanced, and the safety is improved performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208731A_ABST
    Figure CN119208731A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and provides a lithium ion secondary battery. In the lithium ion secondary battery, a negative plate comprises a negative active material, and the negative active material comprises a carbon material and a silicon material; the silicon material comprises a silicon-carbon composite material; based on the total mass of the negative electrode active material, the mass percentage content of the silicon-carbon composite material is recorded as b; the ratio of the mass percentage content x of the silicon element in the first region of the silicon-carbon composite material to the mass percentage content y of the silicon element in the second region is marked as B, and B is more than 0 and less than 1; the electrolyte comprises lithium bis (fluorosulfonyl) imide and fluoroethylene carbonate; on the basis of the total mass of the electrolyte, the mass percentage content of the lithium bis (fluorosulfonyl) imide is recorded as m1, and the mass percentage content of the fluoroethylene carbonate is recorded as m2; and when B, b, m1 and m2 meet the relational expression [(m1 + m2) / B] * b > = 0.2, the battery can give consideration to high energy density, low thickness swelling rate and rapid charging capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium ion secondary battery. Background Art

[0002] The development background of high-voltage lithium-ion battery electrolytes is mainly due to the pursuit of higher energy density and higher safety performance. With the development of science and technology and the increase in market demand, the application field of lithium-ion batteries is expanding day by day, from consumer electronics to electric vehicles, energy storage systems and other fields, and the requirements for battery performance are getting higher and higher. At present, the negative electrode active materials in commercial lithium-ion batteries are mainly graphite materials, but the actual gram capacity of existing graphite materials is low (within 360mAh / g) and is close to its theoretical limit (372mAh / g), and the development space is limited. Silicon-based materials have ultra-high theoretical specific capacity (4200mAh / g) and are one of the ideal materials for further improving the energy density of lithium-ion batteries. However, the existing silicon-based materials have a large volume expansion of particles during the charging and discharging process, which makes the volume energy density of lithium-ion batteries low, and easily causes the problems of fast battery cycle decay and large volume change rate; at the same time, the lithium ion diffusion coefficient of silicon-based materials is low, which limits the fast charging ability of silicon-containing lithium-ion batteries.

[0003] As the voltage continues to increase (>4.55V), the positive electrode active material releases oxygen, which intensifies the oxidation of the electrolyte, leading to solvent decomposition and gas production. The decomposition of lithium salts will also continue to increase, generating more HF, destroying the SEI film (solid electrolyte interface film) and corroding the electrode material; at the same time, the transition metal ions of the positive electrode continue to dissolve and migrate to the surface of the negative electrode, causing certain damage to the negative electrode interface film.

[0004] Therefore, the development background of lithium-ion battery electrolytes is closely related to the urgent need of today's society for efficient, environmentally friendly and safe energy storage and conversion technologies. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a lithium ion secondary battery, in which a silicon-carbon composite material is added to the negative electrode sheet, the silicon content of the silicon-carbon composite material is gradiently distributed from the center to the surface, and an electrolyte containing lithium bis(fluorosulfonyl)imide and fluoroethylene carbonate is used in combination. By adjusting the mass percentage of lithium bis(fluorosulfonyl)imide, the mass percentage of fluoroethylene carbonate, the mass percentage of the silicon-carbon composite material, and the mass percentage ratio of the silicon element in the first region and the second region of the silicon-carbon composite material to meet a specific relationship, the dissolution problem of the positive electrode material under high voltage can be solved, the cycle stability and high temperature storage performance of the battery under high voltage can be improved, and high energy density, low thickness expansion rate and fast charging capability can be taken into account.

[0006] In order to achieve the above object, the present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0007] The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a carbon material and a silicon material; the silicon material includes a silicon-carbon composite material; based on the total mass of the negative electrode active material, the mass percentage of the silicon-carbon composite material is recorded as b;

[0008] The mass percentage of silicon in the first region of the silicon-carbon composite material is recorded as x, the mass percentage of silicon in the second region is recorded as y, the ratio of y to x is recorded as B, 0<B<1;

[0009] The electrolyte includes an electrolyte lithium salt, and the electrolyte lithium salt includes lithium bis(fluorosulfonyl)imide; based on the total mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is recorded as m1;

[0010] The electrolyte includes a first additive, wherein the first additive includes fluoroethylene carbonate, and the mass percentage of the fluoroethylene carbonate is recorded as m2 based on the total mass of the electrolyte;

[0011] B, b, m1 and m2 satisfy the relationship: [(m1+m2) / B]*b≥0.2.

[0012] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0013] The lithium ion secondary battery provided by the present invention has a silicon-carbon composite material in the negative electrode sheet of the battery with a small volume expansion rate. By adding lithium bis(fluorosulfonyl)imide and fluoroethylene carbonate to the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide in the electrolyte (m1), the mass percentage of fluoroethylene carbonate (m2), the mass percentage of silicon-carbon composite material in the negative electrode active material (b) and the mass percentage ratio of silicon element in the first region and the second region of the silicon-carbon composite material (B) are adjusted. When [(m1+m2) / B]*b≥0.2, the dissolution problem of positive electrode material under high voltage can be solved, the cycle stability and high temperature storage performance of the battery under high voltage can be improved, and high energy density, low thickness expansion rate and fast charging capability are taken into account.

[0014] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Shown is a schematic cross-sectional view of a silicon-carbon composite material.

[0016] Reference numerals: 1 - first region; 2 - second region. DETAILED DESCRIPTION

[0017] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0018] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0019] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.

[0020] In the present invention, the term "lithium dendrite" refers to an undesirable phenomenon that may occur during fast charging, which may pierce the separator and cause a short circuit in the battery.

[0021] In the present invention, the term "Dv50" refers to the particle size corresponding to when the cumulative volume particle size distribution percentage of a sample reaches 50%. Dv50 can be tested using a laser particle size analyzer.

[0022] In the present invention, the term "closed pores" refers to tiny, closed pore structures existing inside the silicon-carbon composite material, and these pores are not connected to the outside of the material.

[0023] In the present invention, the term "HOMO value" refers to the energy value of the highest occupied molecular orbital, which is the energy of the highest energy level orbital occupied by electrons in a molecule.

[0024] The present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0025] The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a carbon material and a silicon material; the silicon material includes a silicon-carbon composite material; based on the total mass of the negative electrode active material, the mass percentage of the silicon-carbon composite material is recorded as b;

[0026] The mass percentage of silicon in the first region of the silicon-carbon composite material is recorded as x, the mass percentage of silicon in the second region is recorded as y, the ratio of y to x is recorded as B, 0<B<1;

[0027] The electrolyte includes an electrolyte lithium salt, and the electrolyte lithium salt includes lithium bis(fluorosulfonyl)imide; based on the total mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is recorded as m1;

[0028] The electrolyte includes a first additive, wherein the first additive includes fluoroethylene carbonate, and the mass percentage of the fluoroethylene carbonate is recorded as m2 based on the total mass of the electrolyte;

[0029] B, b, m1 and m2 satisfy the relationship: [(m1+m2) / B]*b≥0.2.

[0030] In the present invention, the mass percentage of silicon is the average content of silicon in the first region or the second region of the silicon-carbon composite material. The test method for the average content of silicon includes: testing at least 5 points in any region of the first region or the second region using a spectrometer point scanning mode to obtain the average value of the silicon content.

[0031] In the present invention, the method for determining the mass percentage b of the silicon-carbon composite material comprises the following steps: using the energy spectrum backscattering point scanning mode to test the silicon and carbon contents in more than 10 silicon-carbon particles, taking the average value of the test results as the silicon-carbon ratio of the silicon-carbon particles, and recording the silicon content therein as ɑ%; then using thermogravimetry to determine the silicon content in the entire negative electrode sheet, and the measured silicon content is recorded as β%; the mass percentage b of the silicon-carbon composite material = β / ɑ.

[0032] The present invention adds fluoroethylene carbonate (FEC) and lithium bis(fluorosulfonyl)imide (LiFSI) to the electrolyte. Fluoroethylene carbonate can inhibit the expansion of the first and second regions of the silicon-carbon composite material in the battery negative electrode sheet during the charge-discharge cycle, so that the silicon-carbon composite material has a smaller volume expansion rate; at the same time, FEC has lower SEI film impedance and charge exchange impedance of the negative electrode. During the battery charging process, the volume deformation of the first region will cause a certain stress to the second region, and the interface film on the surface of the negative electrode is also squeezed by the stress, causing the SEI film to be damaged; further adding lithium bis(fluorosulfonyl)imide to the electrolyte can help repair the solid electrolyte interface SEI film layer formed on the outer layer of the second region, prevent lithium ions in the electrolyte from directly contacting the negative electrode material, and slow down the volume expansion of the negative electrode material.

[0033] In addition to solving the above-mentioned problems, the fluoroethylene carbonate and lithium bis(fluorosulfonyl)imide in the electrolyte are used in combination with the silicon-carbon composite material in the negative electrode, and B, b, m1 and m2 are adjusted to satisfy the relationship [(m1+m2) / B]*b≥0.2. This can promote the formation of the SEI film by reducing the viscosity of the electrolyte and the impedance of the interface, improve the wetting effect of the electrolyte on the silicon-containing negative electrode, and enable the electrolyte to cover the negative electrode surface more evenly, thereby improving the overall performance of the battery. Further, the battery has a higher volume energy density, a higher cycle retention rate, a lower thickness expansion rate and a better rapid discharge capability.

[0034] Furthermore, lithium dendrites are prone to form on the silicon-carbon negative electrode during fast charging of the battery. Adding fluoroethylene carbonate to the electrolyte can reduce the risk of lithium dendrite growth by stabilizing the SEI film and reducing the internal impedance of the battery, reducing the risk of lithium dendrites piercing the diaphragm and causing a battery short circuit, and improving the safety performance of the battery.

[0035] If the mass percentage y of silicon in the second region of the silicon-carbon composite material is greater than the mass percentage x of silicon in the first region, that is, y>x, the silicon content inside the silicon-carbon composite material is higher than the surface, and the expansion stress is concentrated inside the silicon-carbon composite material, making the composite material easy to break during the lithium insertion and extraction process, resulting in a poor cycle retention rate of the battery. To overcome the above problems, the relationship between x and y should satisfy y<x, that is, the ratio B of y to x should satisfy 0<B<1, for example, B can be 0, 0.001, 0.003, 0.005, 0.008, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.66, 0.7, 0.8, 0.9, 0.99 or any point value in the range composed of the above two point values, preferably 0.2≤B≤0.8, and further preferably 0.2≤B≤0.66.

[0036] like Figure 1 As shown, the silicon-carbon composite material includes a first region (1) and a second region (2), wherein the first region (1) refers to a region of 0.01-0.5 μm from the edge to the core of the cross section of the silicon-carbon composite material, and the second region (2) refers to a region of the cross section of the silicon-carbon composite material that is more than 0.5 μm away from the edge.

[0037] In some embodiments, the mass percentage content b of the silicon-carbon composite material satisfies: 3%≤b≤99%, for example, the value of b can be 3%, 5%, 8%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 93%, 96%, 99% or any point value in the range composed of the above two point values, preferably 5%≤b≤50%. When B, b, m1 and m2 satisfy [(m1+m2) / B]*b≥0.2, when the mass percentage content b of the silicon-carbon composite material is adjusted to meet the above range, it can be avoided that when b is less than 3%, the gram capacity of the silicon-carbon composite material is low and the volume energy density of the battery is low; it can also be avoided that when b is greater than 99%, the volume expansion of the silicon-carbon composite material is large, the structural stability of the silicon-carbon composite material is poor, resulting in poor cycle retention rate of the battery and high thickness expansion rate. Therefore, the energy density and expansion rate of the battery are further taken into account, so that the battery has a higher energy density and a lower thickness expansion rate.

[0038] In some embodiments, the mass percentage content m1 of lithium bis(fluorosulfonyl)imide satisfies: 5%≤m1≤20%; for example, the value of m1 can be 5%, 8%, 10%, 12%, 14%, 16%, 18%, 20% or any point value in the range of the above two point values. When B, b, m1 and m2 satisfy [(m1+m2) / B]*b≥0.2, when the mass percentage content m1 of lithium bis(fluorosulfonyl)imide is adjusted to meet the above range, the SEI film layer formed on the outer layer of the silicon-containing negative electrode can be better repaired, and the lithium ions in the electrolyte are further prevented from directly contacting the negative electrode material, and the volume expansion of the negative electrode material is slowed down.

[0039] In some embodiments, the mass percentage content m2 of fluoroethylene carbonate satisfies: 3%≤m2≤20%; for example, the value of m2 can be 3%, 5%, 8%, 10%, 12%, 14%, 16%, 18%, 20% or any point value in the range of the above two point values. When B, b, m1 and m2 satisfy [(m1+m2) / B]*b≥0.2, when the mass percentage content m2 of fluoroethylene carbonate is adjusted to meet the above range, the expansion of the negative electrode of the battery during the charge and discharge cycle can be better suppressed, and the SEI film impedance and charge exchange impedance of the negative electrode are lower. At the same time, the internal impedance of the battery can be further reduced, and the risk of lithium dendrites piercing the diaphragm and causing a short circuit in the battery can be reduced, thereby improving the safety performance of the battery.

[0040] It should be noted that when calculating the value of the formula [(m1+m2) / B]*b, when m1, m2, and b are expressed in percentage, they are all converted into decimals when substituted into the formula for calculation. For example, when m1=20%, m2=20%, and b=60%, and B=0.02, [(m1+m2) / B]*b=[(0.2+0.2) / 0.02]*0.6=12.

[0041] In order to improve the energy density of the battery, the existing technology often increases the silicon doping ratio of the battery negative electrode material. Under certain conditions, the appropriate amount of silicon doping may help promote the graphitization process, making the graphite crystal structure more perfect, thereby increasing the OI value. However, although increasing the silicon content of the negative electrode material can bring higher specific capacity, the high proportion of silicon content will also cause the battery system to expand significantly, affecting the safety performance of the battery.

[0042] In order to further improve the safety performance of the battery, the present invention further proposes: in the lithium-ion secondary battery, the OI value of the negative electrode active material is denoted as A, and A, b and B are limited to satisfy the relationship: B*b*A≥3, and the value of B*b*A can be any value greater than or equal to 3, for example, it can be 3, 4, 5, 6, 7, 8, etc.

[0043] From the attached picture Figure 1 It can be seen that the second region of the silicon-carbon composite material is larger than the first region, and because y<x, the average silicon content of the first region is higher than the average silicon content of the second region. When the mass percentage b of the silicon-carbon composite material increases, the average silicon content of the first region has a higher increase relative to the average silicon content of the second region, resulting in a relatively smaller ratio B of y to x. Therefore, in the formula, as the mass percentage b of the silicon-carbon composite material increases, the ratio B of the mass percentage of silicon in the second region to the first region decreases, that is, b is negatively correlated with B.

[0044] In the present invention, by changing the mass percentage b of the silicon-carbon composite material in the negative electrode active material, the ratio B of the mass percentage of the silicon element in the second region to the first region, and regulating the OI value of the negative electrode active material to satisfy the relationship: When B*b*A≥3, as the content b of the silicon-carbon composite material increases, the ratio B of the average silicon content in the second region to the first region decreases. The increase in b is beneficial to improving the specific capacity of the battery, but the larger the b, the larger the expansion of the battery system, which affects the safety performance of the battery. Since the silicon content in the second region of the silicon-carbon composite material is low and there are more pores, while bringing a higher specific capacity, the expansion of the particles inside the silicon-carbon composite material when reacting with lithium is small, and the expansion effect caused by the increase in b can also be partially buffered by the pores inside the silicon-carbon composite material. At the same time, the silicon-carbon composite material has a higher structural stability, so that the negative electrode active material has a relatively low OI value. Therefore, when B*b*A≥3, the battery can reduce the thickness expansion of the battery under a high voltage (>4.55V) system and improve the safety performance of the battery.

[0045] In some embodiments, the OI value A of the negative electrode active material is controlled to be 5-30, and the value of A can be, for example, 5, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30 or any point value in the range formed by any two of the above point values. When A, b and B satisfy the relationship B*b*A≥3, and the OI value of the negative electrode active material is adjusted to the above range, the battery energy density can be improved while avoiding the large expansion of the battery system caused by the excessive silicon content of the negative electrode sheet, thereby improving the safety performance of the battery.

[0046] In the present invention, the test method of the OI value A specifically comprises the following steps: after discharging the lithium-ion secondary battery to 0% SOC, disassembling and removing the negative electrode plate, soaking it in a dimethyl carbonate (DMC) solvent for 12 hours and then rinsing it with DMC to remove the lithium salt attached to the plate, and testing it with an X-ray powder diffraction instrument (such as Shimadzu XRD-6100 X-ray diffractometer) after drying. The diffraction peak appearing at 2θ=54°-55° in the obtained diffraction spectrum is the (004) peak of graphite, and the intensity is recorded as I 004 , the diffraction peak at 2θ = 77°-78° is the (110) peak of graphite, and its intensity is recorded as I 110 , the OI value A of the negative electrode is I 004 / I 110 .

[0047] In silicon-carbon composite materials, a higher true density means that there are more active materials per unit volume, which helps to increase the energy density of the battery. However, when the true density is high, cracks are more likely to occur during the preparation of the silicon-carbon composite material. This is mainly because the high-density silicon-carbon composite material is subjected to greater stress during processing, which increases the risk of cracks. The presence of cracks will seriously affect the cycle life and safety of the battery. In addition, a larger true density will also limit the transmission of charge within the silicon-carbon composite material, resulting in blockage or elongation of the charge transmission path, thereby reducing the battery's charge and discharge efficiency and power output.

[0048] In order to further improve the charge and discharge efficiency of the battery and reduce the risk of lithium plating, the present invention further proposes that in the lithium-ion secondary battery, the true density of the silicon-carbon composite material is recorded as ρ, and ρ and B satisfy the relationship: 0.3≤ρ*B≤0.7. It can be seen from the above that the mass percentage b of the silicon-carbon composite material is inversely proportional to the mass percentage ratio B of the silicon element in the first region and the second region. Since the density of silicon is greater than that of carbon, the b value increases, the true density ρ of the silicon-carbon composite material increases, and B decreases, that is, ρ is negatively correlated with B. When ρ and B satisfy 0.3≤ρ*B≤0.7, the structure of the silicon-carbon composite material can be made tighter, which helps to reduce the permeability of lithium ions to the negative electrode material during the charge and discharge process, improve the ion transmission efficiency, and effectively control the distribution of lithium ions inside the battery, thereby improving the charge and discharge efficiency of the battery and reducing the risk of lithium plating.

[0049] In some embodiments, p satisfies: 1.4 g / cm 3 ≤ρ≤2.2g / cm 3 , the value of ρ can be, for example, 1.4 g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 Or any point value in the range formed by the above two point values. When ρ and B satisfy 0.3≤ρ*B≤0.7, and ρ is adjusted to meet the above conditions, the silicon-carbon composite material contains an appropriate volume of closed pores, and the size of the closed pores is between 5nm-80nm (for example, 5nm, 6nm, 8nm, 10nm, 12nm, 16nm, 20nm, 25nm, 30nm, 40nm, 50nm, 60nm, 70nm, 75nm, 77nm, 78nm, 79nm, 80nm or any point value in the range formed by the above two point values); when ρ<1.4, the closed pore content of the composite material is relatively high, which easily makes the volume energy density of the battery low; when ρ>2.2, the closed pore content of the composite material is relatively low, the efficiency of the volume effect of the buffer active silicon during lithium insertion and extraction is low, the volume expansion rate of the silicon-carbon composite material is relatively high, and the expansion rate of the negative electrode sheet and the thickness expansion rate of the battery are relatively high. Therefore, when ρ and B satisfy *B≥1, adjusting ρ to meet the above conditions can further improve the battery's charge and discharge efficiency and further reduce the risk of lithium plating.

[0050] In the present invention, the size of the closed pores can be characterized and measured by a variety of methods, such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), etc. Other methods or forms that can visually observe the morphology and size of the closed pores can also be used to characterize and measure the size of the closed pores.

[0051] In some embodiments, in the silicon-carbon composite material, the mass percentage x of the silicon element in the first region satisfies: 60% ≤ x ≤ 83%, for example, x can be 60%, 65%, 70%, 75%, 80%, 83% or any point value in the range composed of any two of the above point values; and / or, the mass percentage y of the silicon element in the second region satisfies: 16% ≤ y ≤ 40%, for example, y can be 16%, 20%, 25%, 30%, 35%, 40% or any point value in the range composed of any two of the above point values.

[0052] In some embodiments, the Dv50 of the silicon-carbon composite material is 3μm-20μm, and the value of Dv50 can be, for example, 3μm, 4μm, 5μm, 6μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, 19μm, 20μm or any point value in the range of the above two point values; more preferably 6μm-12μm. When the particle size of the silicon-carbon composite material is within the above range, it can optimize the electrode structure of the silicon-carbon composite material, reduce the volume expansion under the high-voltage system, help reduce the silicon-carbon composite stress of the material, and achieve the technical effect of optimizing battery performance, ion transfer rate and structural stability.

[0053] The Dv50 value can be determined by a laser particle size test method. For example, the measurement is performed using a Malvern particle size tester, and the specific test steps include: dispersing the silicon-carbon composite material in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether, with a content of 0.02-0.03 wt%) to form a mixture, ultrasonicating the mixture for 2-5 minutes, and then placing it in a Malvern particle size tester for testing.

[0054] In some embodiments, the electrolyte further comprises other fluorinated solvents except fluorinated ethylene carbonate. The fluorinated solvent has a relatively low surface tension, and preferably, the surface tension of the fluorinated solvent is 3mN / m-30mN / m, for example, 3mN / m, 6mN / m, 9mN / m, 12mN / m, 15mN / m, 18mN / m, 21mN / m, 24mN / m, 27mN / m, 30mN / m or any point value in the range of the above two point values, preferably 3mN / m-10mN / m, for example, 3mN / m, 4mN / m, 5mN / m, 6mN / m, 7mN / m, 8mN / m, 9mN / m, 10mN / m or any point value in the range of the above two point values. Fluorinated solvents with low surface tension help to better infiltrate the outer surface layer (first area) of the negative electrode silicon-carbon composite material. The low surface tension makes it easier for solvent molecules to spread on the surface of the silicon negative electrode to form a uniform covering layer, thereby reducing the interface resistance between the silicon negative electrode and the electrolyte, further improving the transmission efficiency of lithium ions, and improving the ionic conductivity of the silicon negative electrode.

[0055] Furthermore, as the battery voltage system increases, the conventional solvents in the electrolyte have insufficient oxidation resistance, while the fluorinated solvents have a lower HOMO value, preferably the HOMO value of the fluorinated solvent is less than -11eV. The lower HOMO value of the fluorinated solvent makes its antioxidant and wetting properties better, and its good wetting effect helps to form a stable SEI film layer on the surface of the silicon-containing negative electrode, which can alleviate the volume expansion change of the silicon-containing negative electrode to a certain extent and improve the cycle stability of the battery.

[0056] Preferably, based on the total mass of the electrolyte, the mass percentage content m3 of the fluorinated solvent satisfies: 5%≤m3≤20%, and the value of m3 can be, for example, 5%, 6%, 7%, 8%, 10%, 12%, 14%, 16%, 17%, 18%, 19%, 20% or any point value in the range composed of any two of the above point values. Adding the fluorinated solvent can increase the solubility of the lithium salt in the electrolyte, improve the chemical stability of the electrolyte, and reduce the decomposition reaction of the electrolyte.

[0057] In some embodiments, the fluorinated solvent includes at least one of fluorinated carbonates, fluorinated carboxylates, and fluorinated ether compounds.

[0058] Illustratively, the fluorocarbonate includes, but is not limited to, at least one of fluoropropylene carbonate, fluoroethyl methyl carbonate, fluorodiethyl carbonate, and fluorodimethyl carbonate.

[0059] Illustratively, the fluorocarboxylic acid ester includes, but is not limited to, at least one of ethyl difluoroacetate DFEA, ethyl trifluoroacetate TFEA, and ethyl trifluoropropionate.

[0060] Exemplarily, the fluoroether compounds include, but are not limited to, at least one of bis(2,2,2-trifluoroethyl) ether, 2,2,2-trifluoroethyl-1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, methyl nonafluorobutyl ether, tris(trifluoroethoxy)methane, and ethyl nonafluorobutyl ether.

[0061] Further, when B, b, m1, and m2 satisfy [(m1 + m2) / B]*b ≥ 0.2, adding a fluorinated solvent to the electrolyte can reduce the interfacial resistance between the silicon negative electrode and the electrolyte, further improve the lithium ion transport efficiency, increase the ionic conductivity of the silicon-containing negative electrode, alleviate the volume change of the silicon-containing negative electrode, and improve the cycle stability of the battery.

[0062] In some embodiments, the carbon material includes at least one of artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon.

[0063] Further, the silicon material optionally includes at least one of nanosilicon, silicon oxide (SiO x , 0 < x < 2), and silicon alloy.

[0064] Further, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a lithium composite oxide; the chemical formula of the lithium composite oxide is Li x Co 1-y Me y O2, where 0.68 < x < 0.74, 0 ≤ y ≤ 0.15, and the doping element Me includes one or more of Al, Mg, Ti, Zr, Ni, Mn, Y, La, Sr, W, Sc, Ce, P, Nb, V, Ta, and Te.

[0065] In some embodiments, the electrolyte further includes a second additive; the second additive includes an ester additive, a nitrile additive, and a sulfonic acid additive; preferably, based on the total mass of the electrolyte, the mass percentage of the second additive is 2% - 20%, for example, it can be 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%.

[0066] Exemplarily, the ester additives in the second additive include, but are not limited to, at least one of vinylene carbonate, vinyl ethylene carbonate, and ethylene sulfate. Adding an ester additive to the electrolyte can reduce the hydrolysis reaction in the electrolyte, improve the battery cycle performance, capacity, and power performance, improve the overall performance of the battery, reduce the gelation tendency of the electrolyte, and extend the battery life.

[0067] Exemplarily, the nitrile additive in the second additive includes, but is not limited to, at least one of succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, sunflower dinitrile, 1,3,6-hexane trinitrile, glycerol trinitrile, 1,2-bis(2-cyanoethoxy)ethane and its derivatives. Adding nitrile additives to the electrolyte can effectively protect the positive electrode material, prevent the electrolyte from being oxidized and decomposed, inhibit the generation of oxides, and reduce possible thermal runaway.

[0068] Exemplarily, the sulfonic acid additive in the second additive includes, but is not limited to, at least one of 1,3-propane sultone, 1-propylene-1,3-sultone, 5-methylthiothiophene 2,2-dioxide, 1,3-propylene sultone, 2,4-butane sultone, 1,4-butane sultone and derivatives thereof. Adding sulfonic acid additives to the electrolyte can enhance the antioxidant properties of the electrolyte, delay the aging process of the electrolyte, improve the stability of the battery and improve the fast charging performance of the battery.

[0069] In some embodiments, the electrolyte includes one or more of carbonate solvents and / or carboxylate solvents; preferably, based on the total mass of the electrolyte, the mass percentage of carbonate solvents and / or carboxylate solvents is 40%-60%, for example, it can be 40%, 44%, 48%, 50%, 52%, 56%, 58%, 60% or any point value in the range of two points above. Adding the carbonate solvent can form a SEI film at the negative electrode, inhibit the side reaction on the electrode surface, and improve the high temperature performance of the battery.

[0070] Illustratively, the carbonate solvent includes, but is not limited to, at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and fluorinated derivatives thereof.

[0071] Exemplarily, the carboxylic acid ester solvent includes, but is not limited to, at least one of propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, ethyl propionate, n-propyl propionate, methyl butyrate, ethyl butyrate and ethyl n-butyrate and derivatives thereof.

[0072] In some embodiments, the electrolyte lithium salt may also include at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl imide), lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyl lithium or lithium bis(trifluoromethylsulfonyl)imide. The above-mentioned lithium salt additive is added to the electrolyte, and the lithium salt additive can improve the ionic conductivity of the electrolyte, make the migration rate of lithium ions in the electrolyte faster, thereby improving the fast charging performance of the battery.

[0073] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0074] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0075] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0076] The batteries of the examples and comparative examples of the present invention were prepared according to the following preparation method, and the differences from Example 1-1 are shown below.

[0077] Example 1-1

[0078] (1) Preparation of positive electrode

[0079] The positive electrode active material Li x Co 1-y Me y O2 (x=0.7, y=0.1, doped with Mn element), polyvinylidene fluoride (PVDF), SP (super P) and carbon nanotubes (CNT) are mixed in a mass ratio of 96:2:1.5:0.5, put into a vacuum mixer, and N-methylpyrrolidone (NMP) is added. The mixture is fully mixed under the action of the vacuum mixer until a uniform and fluid positive electrode slurry is formed, wherein the solid content is 55wt%; the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12μm, dried, rolled, slit and punched to obtain a positive electrode sheet.

[0080] (2) Preparation of negative electrode sheet

[0081] A silicon-carbon composite material (the mass percentage x of the silicon element in the first region and the mass percentage y of the silicon element in the second region are 77% and 23%, respectively), artificial graphite, sodium carboxymethyl cellulose, styrene-butadiene rubber, conductive carbon black and carbon nanotubes are put into a vacuum mixer in a mass ratio of 40:64.5:2.5:1.5:1:0.5, deionized water is added, and the mixture is fully mixed under the action of the vacuum mixer to finally form a uniform, fluid negative electrode slurry with a solid content of 45wt%; the negative electrode slurry is evenly coated on a copper foil with a thickness of 6μm, dried, rolled and die-cut to obtain a negative electrode sheet.

[0082] (3) Preparation of electrolyte

[0083] In an argon glove box with a water content of <0.1ppm and an oxygen content of <0.1ppm, ethylene carbonate (EC), propylene carbonate (PC), fluoroethyl methyl carbonate (FEMC), propyl propionate (PP), and fluoroethylene carbonate (FEC) are uniformly mixed, and fully dried lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI) are added thereto for stirring and dissolution, wherein the amount of LiPF6 added is 12.5% ​​and the amount of LiFSI added is 15% based on the total mass of the electrolyte, and then 4% of 1,3-propane sultone, 2.5% of 1,3,6-hexanetrinitrile, 2% of adiponitrile (ADN), and 2% of succinonitrile (SN) are added based on the total mass of the electrolyte. 1%, stir evenly, the mass proportion of FEC in the electrolyte is 10%, the mass proportion of FEMC in the electrolyte is 15%, and the total mass proportion of EC, PC and PP (the mass ratio of the three is 1:2:4) in the electrolyte can be obtained by calculation. After passing the physical property test, the electrolyte is obtained.

[0084] (4) Preparation of batteries

[0085] The positive electrode sheet obtained in step (1), the negative electrode sheet obtained in step (2) and the separator (8 μm thick polyethylene separator provided by Asahi Kasei Corporation) are wound to obtain a bare battery cell; the bare battery cell is welded with a pole ear and placed in a battery casing, and the electrolyte prepared in step (3) is injected into the dried and qualified battery cell, and a battery is obtained after standing, aging, formation, exhaust, aging, sorting and other processes.

[0086] (5) Test battery

[0087] Electrochemical performance test: The electrochemical performance test is carried out using the following test methods using a Blue Electric charge and discharge test cabinet:

[0088] (i) High temperature storage test

[0089] The batteries prepared in the examples and comparative examples were subjected to high temperature storage tests. The specific test method is as follows: at 25°C ± 5°C, the sample voltage, internal resistance and thickness d0 were tested.

[0090] Step 1: Let stand at 25℃±5℃ for 10 minutes;

[0091] Step 2: 0.2C discharge to the lower limit voltage (3.0V); let stand for 10 minutes;

[0092] Step 3: Charge at 0.7C to the upper voltage limit (4.55V), cut off at 0.05C, and let stand for 10 minutes;

[0093] Step 4: 0.2C discharge to the lower limit voltage (for initial capacity test);

[0094] Step 5: Let stand for 10 minutes;

[0095] Step 6: Charge at 0.7C to the upper voltage limit, and cut off at 0.05C;

[0096] Step 7: Let stand for 10 minutes;

[0097] Step 8: Store at 85℃±2℃ for 6h;

[0098] After storage, take out the sample and immediately test the thermal thickness d1, and calculate the thickness change rate: (d1-d0) / d0.

[0099] (ii) Wettability test

[0100] The test method uses the immersion time method to evaluate the wettability by measuring the time required for the electrolyte to completely penetrate the negative electrode. The specific steps are as follows:

[0101] (1) Take a certain amount of electrolyte and add it to the negative electrode.

[0102] (2) Record the time required for the electrolyte to completely penetrate the solid.

[0103] (3) Evaluate the electrolyte wetting performance of different solids or under different conditions by time difference.

[0104] (iii) Fast charge capacity retention rate

[0105] Cycle test: The batteries prepared in the examples and comparative examples were subjected to cycle test. The specific test method is as follows: At 45°C, the battery was subjected to constant current charge and discharge cycles at a rate of 1C within the charge and discharge cut-off voltage range (3.0V-4.55V) for 600 cycles; the discharge capacity Q1 of the first week and the discharge capacity Q of the 600th week were recorded. 600 , via Q 600 / Q1×100% was used to calculate the capacity retention rate and thickness expansion rate after 600 cycles at 45°C.

[0106] (iv) Lithium deposition test

[0107] The battery interface after 600T of cycle was disassembled to observe whether there was lithium deposition on the negative electrode.

[0108] (v) Safety performance

[0109] Oven temperature test: The batteries prepared in the examples and comparative examples were subjected to oven temperature test. The specific test method is as follows:

[0110] 1) Discharge at 0.2C at 25°C, then charge at 0.5C to the specified voltage of 4.55V;

[0111] 2) Test the full-charge voltage, internal resistance and thickness at 25°C;

[0112] 3) Hang the fully charged battery in a gravity convection or circulating air oven at 25°C (heat transfer is not allowed for non-integrated battery components). Note that the voltage and temperature leads must be properly insulated (to avoid short circuits). Start from room temperature (25°C) and heat up to 132°C at (5±2)°C / min. Place at 132°C for 60 minutes and observe whether the battery catches fire or explodes. If the battery does not catch fire or explode, it is judged that the furnace temperature test has passed. If the battery catches fire or explodes, it is judged that the furnace temperature test has failed.

[0113] Example 1-4 and Comparative Examples 1-3 were carried out with reference to Example 1-1, and the main differences are shown in Table 1. In Example 1, the mass percentage of LiFSI in the electrolyte was changed; in Example 2, the mass percentage of FEC was changed; in Example 3, the ratio of the mass percentage of silicon in the second region to the mass percentage of silicon in the first region of the silicon-carbon composite material was changed; in Example 4, the mass percentage of silicon-carbon composite material was changed; in Comparative Example 1, the mass percentage of silicon-carbon composite material b was too small; in Comparative Example 2, the ratio of the mass percentage of silicon in the second region to the mass percentage of silicon in the first region B>1; in Comparative Example 3, the mass percentage of LiFSI was too small.

[0114] Table 1

[0115]

[0116]

[0117] Note: m1, m2, and b are all converted into decimals and substituted into the formula.

[0118] As can be seen from Table 1, the present invention can solve the dissolution problem of the positive electrode material under high voltage, improve the cycle stability and high temperature storage performance of the battery under high voltage, and take into account high energy density, low thickness expansion rate and fast charging capability by adjusting the mass percentage of lithium bis(fluorosulfonyl)imide (m1) in the electrolyte, the mass percentage of fluoroethylene carbonate (m2), the mass percentage of silicon-carbon composite material in the negative electrode active material (b) in the negative electrode sheet, and the mass percentage ratio of silicon element in the first region and the second region in the silicon-carbon composite material (B) to meet [(m1+m2) / B]*b≥0.2.

[0119] The Example 5 group was carried out in accordance with the Example 1-1, and the main differences are shown in Table 2. In the Example 5 group, the OI value of the negative electrode sheet was changed.

[0120] Table 2

[0121]

[0122] It can be seen from Table 2 that the present invention can avoid large expansion of the battery system caused by excessive silicon content in the negative electrode sheet by adjusting the OI value (A) of the negative electrode sheet, and when the mass percentage content of the silicon-carbon composite material (b) and the mass percentage content ratio of the silicon element in the first region and the second region in the composite material (B) satisfy B*b*A≥3, thereby improving the safety performance of the battery.

[0123] The Example 6 group was carried out with reference to the Example 1-1, and the main differences are shown in Table 3. In the Example 6 group, the true density of the silicon-carbon composite material was changed.

[0124] Table 3

[0125]

[0126] It can be seen from Table 3 that the present invention can improve the ion transmission efficiency, enhance the charge and discharge efficiency of the battery and reduce the risk of lithium plating by adjusting the true density (ρ) of the silicon-carbon composite material and the mass percentage ratio (B) of the silicon-carbon composite material in the first region and the second region to satisfy 0.3≤ρ*B≤0.7.

[0127] Example 7 was carried out with reference to Example 1-1, and the main differences are shown in Table 4. In Example 7, the Dv50 of the silicon-carbon composite material was changed.

[0128] Table 4

[0129]

[0130] It can be seen from Table 4 that the present invention can reduce the volume expansion under high-pressure system, reduce the silicon-carbon composite stress of the material, and optimize the battery performance, ion transfer rate and structural stability by adjusting the Dv50 of the silicon-carbon composite material.

[0131] Example 8 and Example 9 were carried out with reference to Example 1-1, and the main differences are shown in Table 5. In Example 8, the mass percentage of the fluorinated solvent was changed, wherein no fluorinated solvent was added to the electrolyte of Example 8-4; and in Example 9, the type of the fluorinated solvent was changed.

[0132] Table 5

[0133]

[0134] Note: “ / ” indicates that the corresponding parameter is not tested.

[0135] It can be seen from Table 5 that the present invention can reduce the interface resistance between the silicon negative electrode and the electrolyte, further improve the transmission efficiency of lithium ions, improve the ionic conductivity of the silicon-containing negative electrode, alleviate the volume change of the silicon-containing negative electrode, and improve the cycle stability of the battery by adding a fluorinated solvent to the electrolyte and adjusting the mass percentage of the fluorinated solvent.

[0136] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0137] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a carbon material and a silicon material; the silicon material includes a silicon-carbon composite material; based on the total mass of the negative electrode active material, the mass percentage of the silicon-carbon composite material is recorded as b; The mass percentage of silicon in the first region of the silicon-carbon composite material is recorded as x, the mass percentage of silicon in the second region is recorded as y, the ratio of y to x is recorded as B, 0<B<1; The electrolyte includes an electrolyte lithium salt, and the electrolyte lithium salt includes lithium bis(fluorosulfonyl)imide; based on the total mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is recorded as m1; The electrolyte includes a first additive, wherein the first additive includes fluoroethylene carbonate, and the mass percentage of the fluoroethylene carbonate is recorded as m2 based on the total mass of the electrolyte; B, b, m1 and m2 satisfy the relationship: [(m1+m2) / B]*b≥0.

2.

2. The lithium ion secondary battery according to claim 1, characterized in that: b satisfies: 3%≤b≤99%, preferably 5%≤b≤50%; Preferably, m1 satisfies: 5%≤m1≤20%; and / or, 3%≤m2≤20%.

3. The lithium ion secondary battery according to claim 1, characterized in that: The OI value of the negative electrode active material is recorded as A, and A, b and B satisfy the relationship: B*b*A≥3; Preferably, the OI value A of the negative electrode active material is 5-30.

4. The lithium-ion secondary battery according to claim 1, characterized in that: The true density of the silicon-carbon composite material is denoted as ρ, and ρ and B satisfy the relationship: 0.3≤ρ*B≤0.7; Preferably, ρ satisfies: 1.4 g / cm 3 ≤ρ≤2.2g / cm 3 .

5. The lithium ion secondary battery according to claim 1, characterized in that: In the silicon-carbon composite material, x satisfies: 60%≤x≤83%; and / or y satisfies: 16%≤y≤40%; Preferably, the Dv50 of the silicon-carbon composite material is 3 μm-20 μm; more preferably 6 μm-12 μm.

6. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that: The electrolyte includes a fluorinated solvent; Preferably, based on the total mass of the electrolyte, the mass percentage content m3 of the fluorinated solvent satisfies: 5%≤m3≤20%.

7. The lithium ion secondary battery according to claim 6, characterized in that: The surface tension of the fluorinated solvent is 3mN / m-30mN / m; and / or the HOMO value of the fluorinated solvent is less than -11eV; Preferably, the fluorinated solvent includes at least one of fluorinated carbonates, fluorinated carboxylates, and fluorinated ether compounds.

8. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that: The carbon material comprises at least one of artificial graphite, natural graphite, mesophase carbon microbeads, hard carbon and soft carbon; Preferably, the silicon material optionally includes at least one of nano-silicon, silicon-oxygen, and silicon alloy; Preferably, the positive electrode sheet comprises a positive electrode active material, wherein the positive electrode active material comprises a lithium composite oxide; the chemical formula of the lithium composite oxide is Li x Co 1-y Me y O2, wherein 0.68<x<0.74, 0≤y≤0.15, and the doping element Me includes one or more of Al, Mg, Ti, Zr, Ni, Mn, Y, La, Sr, W, Sc, Ce, P, Nb, V, Ta, and Te.

9. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that: The electrolyte further includes a second additive; the second additive includes an ester additive, a nitrile additive, and a sulfonic acid additive; Preferably, based on the total mass of the electrolyte, the mass percentage of the second additive is 2%-20%.

10. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that: The electrolyte includes one or more of a carbonate solvent and / or a carboxylate solvent; Preferably, based on the total mass of the electrolyte, the mass percentage of the carbonate solvent and / or the carboxylate solvent is 40%-60%.

Citation Information

Patent Citations

  • Additive-containing lithium salt electrolyte

    CN108767318A

  • Electrolyte adaptive to silicon-carbon negative electrode and lithium ion battery

    CN111048834A

  • Electrolyte for silicon negative electrode battery and lithium ion battery

    CN116031487A

  • Electrolyte suitable for silicon-carbon negative electrode and electrochemical device and electronic equipment comprising same

    CN116885275A

  • Secondary battery containing silicon-based negative electrode

    CN117080361A

Cited By

  • Negative plate, battery and electric equipment

    CN122474574A

  • Lithium-ion secondary battery

    WO2026061124A1